PENINGKATAN AKTIVITAS SELULASE PADA TANAH HUTAN MANGROVE PANTAI SUWUNG BALI DENGAN PENGAYAAN SUBTRAT SELULOSA JANUR KELAPA (Cocos nucifera) - Kurniawati, Ika; Wirajana, I Nengah; Mahardika, I Gede (Jurnal Kimia (Journal of Chemistry); Vol. 7, No. 1 Januari 2013DO - 10.24843/JCHEM.2013.v07.i01.p10)
The aim of this study is to determine the effect of coconut ( Cocos nucifera ) leaf enrichment to soil of mangrove forest of Bali Suwung coastal on the cellulase activity. The measurement of cellulase activity was conducted by CMC method ( Carboxymethyl Cellulose Assay ) on soil sample with and without enrichment of coconut leaf substrate in incubation time of 1, 2, 3, and 4 weeks. The results showed that the enrichment increased cellulase activity. In addition, cellulase activited the soil samples, increase with incubation times.
Keywords: Cellulase, mangrove soil, Carboxymethyl Cellulose Assay